Self‐healing and energy‐efficient restoration in machine‐to‐machine networks. Issue 7 (1st May 2016) - Zeng, Yali; Chen, Zhide; Yang, Xu
Abstract : Machine‐to‐machine (M2M) networks often serve mission‐critical applications in our daily life. Maintaining nodes connectivity is crucial for M2M networks to accomplish their tasks effectively. The fault of a critical node may break the network into several blocks, and thus hinders the operation. Rapid recovery is highly required in such a case. In this study, the authors focus on designing an effective algorithm for restoring damaged network topologies by moving available nodes. Unlike contemporary algorithms that only consider network connectivity or coverage, the proposed algorithm not only takes into account network connectivity, coverage and energy consumption, but also concerns about the shortest path between any pair of nodes. Simulation results demonstrate that the proposed algorithm outperforms the existing scheme in terms of network lifetime.